2017
DOI: 10.1021/acs.jpcc.7b03415
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Trifluoroacetic Acid in Amorphous Solid Water: Charge-Delocalized Hydroniums and Zundel Continuum Absorption

Abstract: We studied the ionic dissociation of trifluoroacetic acid (TFA) in D2O amorphous solid water (ASW) using reflection absorption infrared spectroscopy, low-energy sputtering, and H/D isotopic exchange experiment. TFA readily dissociated to hydronium and counterions in ASW at 60 K, which indicates a significant increase in the acidity as compared with that in aqueous solution at room temperature. The acid dissociation produced a Zundel continuum band in the 1000–3000 cm–1 region and an accompanying lowered intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…At 140 K, the spectrum showed other minor changes (Supporting Information Figure S1), including the change of the bulk ν(O−D) band shape due to the crystallization of ice 6 and the increase in the ν(O−H) band of HDO due to H/D exchange reactions. 10,11 These observations showed that the spontaneity of acid dissociation was unaffected by temperature changes between 8 and 140 K.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…At 140 K, the spectrum showed other minor changes (Supporting Information Figure S1), including the change of the bulk ν(O−D) band shape due to the crystallization of ice 6 and the increase in the ν(O−H) band of HDO due to H/D exchange reactions. 10,11 These observations showed that the spontaneity of acid dissociation was unaffected by temperature changes between 8 and 140 K.…”
mentioning
confidence: 89%
“…Acetic acid (AA; pK aq = 4.76) did not dissociate in ice either. 11 These observations located the boundary of spontaneous dissociation of carboxylic acids in ice to be between pK aq = 2.82 and 3.75 in terms of the acidity scale in aqueous phase.…”
mentioning
confidence: 97%
See 3 more Smart Citations